Load Balancing in Distributed System - Hasani , Nahla Flayyih (International Journal of Basic and Applied Sciences, 2025)
Scalability is a critical requirement for distributed systems, especially as the number of users and their demands grow. This paper reviews ‎and compares various load balancing techniques, which are essential for ensuring efficient server resource utilization. We examine both ‎static and dynamic load balancing methods, highlighting their properties, operational procedures, advantages, and limitations. A comparative ‎analysis is provided to assist in selecting the appropriate technique for different application scenarios‎.